Elevating Recycling Standards: Global Requirements for Plastic Traceability and Quality Testing - Gazeau, Benjamin; Minunno, Roberto; Zaman, Atiq; Shaikh, Faiz (MDPI, 2024)
Globally, we produced 489 million tonnes of plastic in 2023 and we recycled only 8.17%. This study navigates the landscape of recycling practices, highlighting the imperative to reevaluate and upgrade industry-standard protocols. The central focus of this study is on integrating more robust traceability criteria and advanced quality testing methodologies to improve recycled plastics with intrinsic value, particularly in anticipation of future market applications. The investigation examines the prevailing industry standard traceability and quality framework. It then assesses the applicability of those standards using technical datasheets for recycled high-density polyethylene resin grades. This study proposes a paradigm shift toward a more sophisticated analytical approach. This comprehensive framework aims to transcend traditional quality and traceability evaluation. This paper employs a mixed methodological approach, including a thematic analysis of relevant industry standard regulations and an in-depth literature review, to address the need for an operational framework for recycling quality. This study highlights that recycling quality depends on technical attributes determining functionality and application suitability. While some properties are measured, the conventional framework does not address the degradation level of recycled plastic. This study concludes with broader considerations, emphasising the need for a traceability model to disclose material history and composition. This study advocates an industry-wide upgrade in recycling standards, prioritising traceability and quality testing. The proposed enhancements in testing grids and the improved understanding of recycling quality collectively contribute to a holistic framework, unlocking the intrinsic value of recycled plastics for future market applications.